The MHD graphene−CMC−water nanofluid past a stretchable wall with Joule heating and velocity slip impact: Coolant application - Rashid, I.; Zubair, T.; Asjad, M. I.; Irshad, S.; Eldin, S. M. (Frontiers in Physics, 2023)
The heat transport mechanism has an engrossing application in effective heat management for the automobile industry and the biomedical industry. The analysis of MHD graphene CMC-water nanofluid past a stretchable wall with Joule heating and velocity slip impact is performed in this regard. A graphene-based nanofluid is considered. The dynamic model is used to simplify the complicated ordinary differential equations into nondimensional forms, which are then evaluated analytically. Numerical data and graphs are produced to analyze the consequences of a physical entity. Moreover, the velocity field is decreased while the magnitude of the magnetic parameter is increased. A decrease in θ(η) is observed as a result of an increase in ϕ. It is noted that a rise in the magnetic parameter causes a fall in the temperature distribution. It is perceived that −f′′(0) is decreased with an augmentation in β_s and the opposite trend is shown for ϕ. The flow regime displays against the viscoelastic parameter.